Public Service Transformation : Improving the Service Quality of Regional Public Companies - Fadhillah Shofa Lucyana; Fiki Azkiya; Tazqiyatas Safira; Siti Khumayah; Khaerudin Imawan (CV. Syntax Corporation Indonesia, 2024)
This research was conducted because there was a decrease in the number of customers of the Tirta Giri Nata Drinking Water Regional Public Company in Cirebon City during the 2021-2023 period. This research uses a qualitative method by collecting data through interviews, observation and documentation. This research uses public service theory which focuses on the five main service quality dimensions related to customer service by public water companies: Tangibles, responsiveness, reliability, assurance and empathy. This study uses an interactive model data analysis procedure, which begins with data collection and continues with data reduction, data visualization, and conclusion drawing as the final step. The results showed that the service quality of PERUMDA Tirta Giri Nata Cirebon City still did not meet the five main success indicators, namely reliability, responsiveness, assurance, empathy, and tangible. The conclusion of this study is that the quality of customer service at PERUMDA Tirta Giri Nata Cirebon City, especially in terms of administrative and technical complaint services, has not yet reached an optimal level. There are still shortcomings in fulfilling the expected dimensions and indicators of service quality.